Upaya Peningkatan Nilai Ekonomi di Desa Piasa Wetan Kecamatan Susukan Kabupaten Banjarnegara Melalui Pengembangan Padi Organik Antosianin Tinggi: Efforts to Increase Economic Value in Piasa Wetan Village, Susukan District, Banjarnegara Regency through the Development of High Anthocyanin Organic Rice - Sholikhah, Ummi; Rahayu, Puji; Fanata, Wahyu Indra Duwi; Handoyo, Tri; Magfiroh, Illia Seldon; Suciati, Luh Putu; Widodo, Nur; Setyawati, Intan Kartika; Ratnasari, Tri; Tanzil, Ahmad Ilham (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Abstract: Piasa Wetan Village, located in Susukan District, Banjarnegara Regency, Central Java, has great potential for cultivating high-anthocyanin rice, supported by a favorable environment. However, limited knowledge and skills among farmers in organic farming practices and the certification process remain challenges. This community service initiative aims to enhance farmers' skills through comprehensive training that includes organic methods, harvest management, and the importance of certification. The training results showed a significant increase in knowledge, from 7% to 100% after the program's completion. More effective cultivation practices are now being implemented, including the selection of high-quality seeds, optimal land preparation, and more efficient harvest and marketing strategies. Certification is expected to help increase market prices, expand access, and ensure sustainability by enforcing strict organic farming standards. With continued education and improved agricultural techniques, Piasa Wetan Village has the potential to become a leading producer of high-anthocyanin rice in Banjarnegara, ultimately increasing farmers' incomes, supporting food security, and providing health benefits to consumers.